Anodic and hydrothermal growth of iron oxide Nanoporous-Nanorod film for chromium removal - Chuah, Chung Zhih (2021)
Hexavalent chromium (Cr (VI)) is a wastewater pollutant which causes detrimental health effects to the surrounding organisms. Cr (VI) removal by adsorption is commonly applied due to its cost-effectiveness and reusability to reduce this wastewater pollution problem. Hematite (α-Fe2O3) is an adsorbent with good Cr (VI) removal properties. To enhance the Cr (VI) removal properties, α-Fe2O3 nanoporousnanorod structure with high surface-to-volume ratio was produced on iron foil substrate. The nanopores and nanorods were produced by anodization and hydrothermal methods, respectively. Both nanopore and nanorod growth were followed by annealing post-treatment. The annealing after nanopore growth was performed at 200–500 °C for 0.5 h to determine the suitable annealing temperature for fabrication of nanoporous-nanorod structure. The crystallinity of nanopores increased with increasing annealing temperature. Temperature of ≥300 °C showed formation of crystalline α- Fe2O3 nanopores and resulted in successful formation of α- Fe2O3 nanoporous-nanorod structure. Sample annealed at 500 °C showed the best Cr removal efficiency of 96.90% in 30 min due to high crystallinity and high amount of nanopores.